Happy childhood: the search for an informative system of characteristics through the prism of eventfulness - Anna V. Kuchenkova; Svetlana N. Mayorova-Shcheglova (Социологическая наука и социальная практика)
The results of a study devoted to identifying the potential of using information about childhood events to explain the subsequent perception of childhood as a happy one are presented. Based on the assumption that the specificity of the eventfulness of the very first stage of life can determine the existence of groups with happy and unhappy childhood according to subjective estimates, a selection of childhood events has been made that most allow differentiating those who evaluate their childhood as happy and unhappy. As an empirical basis, the results of a survey of representatives of a youth group who have crossed the age of majority or are on its border are used. Among the 100 initial childhood events for analysis, groups of life episodes were identified, the presence and age of occurrence of which are associated with a retrospective assessment of childhood as happy. These are events related to the manifestation of subjectivity and its recognition by adults; consumer and financial socialization ; establishing relationships with peers and parents; independent movements and mobility; a variety of leisure practices and prosocial behavior; some manifestations of infantilism; the absence or later onset of certain traumatic events, deviant behavior practices, actions to change appearance. The listed groups of life episodes form the basis of an informative system of characteristics of a subjectively prosperous childhood and can be used in the future to implement models of multidimensional analysis.